Congregations as providers of social service and HIV / AIDS care - Hendriks, H. J.; Erasmus, J. C.; Mans, G. G. (Dutch Reformed Theological Journal = Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The article argues that the missional identity of the church compels it in a context of poverty and HIV / AIDS to partake in social service ministries. It describes and illustrates the methodology of a multi-disciplinary, participatory action, praxis-oriented research project. The church (and other NGOs) took the lead and addressed poverty related issues in collaboration with the government and business sectors. The different faces of poverty were mapped in the Paarl community highlighting the HIV / AIDS situation and describing the preliminary results of the project
Free